Pengaruh perkembangan AI terhadap dunia pendidikan khususnya pada mahasiswa - Gunawan, Gunawan (Maliki Interdisciplinary Journal, 2024)
In the current era, the rapid development of technology has had a big influence on all aspects of life, for example, in the economic aspect, traders and consumers no longer have to meet in person to make transactions, but simply by using an application transactions can be carried out. This is a concrete example that shows that technological developments can change human activities to make them easier to carry out. And the same goes for other aspects of life such as education, politics, agriculture and so on. In discussing this article, what we will discuss is the influence of the development of information and communication technology on the world of education. Every day the development of communication and information technology becomes more sophisticated. With this development, it can make all activities or student activities easier, for example in the learning system students can do online-based lectures if there are obstacles to carrying out offline learning, it will also be easier for students to find reference sources. However, on the other hand, the ease that we can experience now will also have a negative impact on students.